The role of microvascular endothelial dysfunction and genetics on severity and progression of primary open angle glaucoma in Malays - Bukhari, Syed Mudassar Imran (2016)
There is lack of knowledge of clinical presentation and risk factor for primary open angle glaucoma (POAG) in Malays. Identification of the risk factors for severity and progression of POAG in Malays is important to strategies prevention of blindness and effective management. This study was conducted to determine the severity and progression of POAG in Malay patients and to determine the role of microvascular endothelial function and genetics in progression and severity of POAG. A cross-sectional study was conducted involving 215 Malay (114 POAG patients and 101 controls) subjects. Progression was determined based on Humphrey visual field analysis (HVF) of 114 POAG patients using combination criteria of Advanced Glaucoma Intervention Study (AGIS) scoring and Hodapp, Parish and Anderson classification. Severity of POAG was based on modified AGIS scoring of HVF. Microvascular endothelial function was assessed using Laser Doppler Fluximetry (LDF) with the process of acetylcholine (ACh) and sodium nitroprusside iontophoresis. Venesection was also conducted. High purity genomic DNA was extracted. Microarray Human Omni Express-12 platform was used to identify genetic markers. rs1392912 and rs1660029 from KALRN gene, and rs1210977of COL9A1 gene were identified as potential markers for progression and microvascularendothelial function. These single nucleotide polymorphisms (SNPs) were then subjected to DNA sequencing. After the mean 4.1(3.0) years of follow up, 35 patients showed evidence of visual field progression. Based on HVF at recruitment, 55 patients were mild, 29 moderate and 30 severe POAG. There was significant reduction of microvascular endothelial function in POAG patients compared to control (p<0.001)). ACh and sodium nitroprusside response was significantly reduced in severe POAG (p<0.001). There was significant reduction of microvascular endothelial function in patients who showed visual field progression (p<0.001). The risk of progression is 4.8 folds (95% CI 1.52, 14.86) in patients with rs1392912GA and 5.8folds (95% CI 1.85, 18.61) in patients with rs1660029AG. However, there was no association betweenrs1210977 of COL9A1 and microvascular endothelial function of Malay patients with POAG The progression rate of POAG in Malay patients was 8.5 patients/year. Microvascular endothelial function play a role in progression and severity of POAG in Malays. rs1392912GA and rs1660029AG of KALRN gene are potential genetic markers for progression of glaucoma. Perhaps, improvement in microvascular endothelial function and early detection of patients with genetic variations of KALRN gene may retard the progression of POAG in Malays.